Thin Film Processes Artifacts on Surface Phenomena and Technological Facets - Thirumalai, Jagannathan (IntechOpen, 2017)
The book Thin Film Processes - Artifacts on Surface Phenomena and Technological Facets presents topics on global advancements in theoretical and experimental facts, instrumentation and practical applications of thin-film material perspectives and its applications. The aspect of this book is associated with the thin-film physics, the methods of deposition, optimization parameters and its wide technological applications. This book is divided into three main sections: Thin Film Deposition Methods: A Synthesis Perspective; Optimization Parameters in the Thin Film Science and Application of Thin Films: A Synergistic Outlook. Collected chapters provide applicable knowledge for a wide range of readers: common men, students and researchers. It was constructed by experts in diverse fields of thin-film science and technology from over 15 research institutes across the globe.